Radiographic measurements of the hoof in generally sound donkeys with emphasis on the front limbs - Wacker, Juliana; Schaus, Kyra; Jandowsky, Anabell; Büttner, Kathrin; Röcken, Michael; Bartmann, Claus Peter; Justus Liebig University Giessen (My University, 2024)
Introduction: Due to the tremendous importance of the hoof for the welfare of equids, plenty of studies have investigated the foot conformation of horses, which can be objectively described by morphometric measurements. Although the foot conformations of horses and donkeys differ, only poor data exists describing the physiological foot conformation of donkeys. The objective of this study was to provide reference values for different radiographic parameters for healthy donkeys. Additionally, this study aimed to evaluate differences between the left and right limb or between the medial and lateral parts of the hoof and the dependence of various parameters on size, age, and weight. Materials and methods: Lateromedial and dorsopalmar radiographs were taken of 46 generally sound donkeys, that were lame-free in walk, following a hoof correction due to their hoof pastern axis. With the help of radiopaque markers, several measurements were performed on the radiographs. The statistical analysis was carried out by determining mean values and standard deviations. All parameters were tested for significant differences between the left and right limbs as well as the medial and lateral hoof parts. The methodology included using a paired T-test after proof of a normal distribution of the data using a Shapiro–Wilk Test. For parameters without a normal distribution, the Wilcoxon rank-sum test was used instead. The dependence of the parameters on height, weight, and age was examined using a Spearman rank correlation. Results: Reference values for the various parameters were provided for an average population of healthy donkeys. For two parameters, heel length and sole thickness, a significant difference between the left and right limb was shown. There was evidence the medial wall angle was significantly bigger than the lateral wall angle (p = 0.0075), whereas the sole thickness was significantly larger on the lateral aspect (p < 0.001). No correlation with age was found for most variables, with a few exceptions. Almost all absolute lengths measured showed a moderate to strong positive correlation with the weight and height of the subject, while most angle measurements were not dependent on these parameters. The data obtained specifically for the donkeys in this study differ substantially from the data already published for horses. Thus, this data serves as a helpful guideline for the assessment of radiographs of the donkey’s foot. All donkeys included in this study were generally sound and lame-free in walk, but there was undeniable evidence of chronic laminitis and not all the values collected can be considered to be physiological.
Keywords: ddc:630